Prompt closure versus gradual weaning of external ventricular drainage for hydrocephalus in adult patients with aneurysmal subarachnoid haemorrhage: a systematic review. Issue 11 (26th November 2020) - Capion, Tenna; Lilja-Cyron, Alexander; Juhler, Marianne; Mathiesen, Tiit Illimar; Wetterslev, Jørn
Abstract : Objectives: To summarise the evidence on benefits and harms of prompt closure versus gradual weaning of external ventricular drainage (EVD) in patients with hydrocephalus following aneurysmal subarachnoid haemorrhage (aSAH) based on randomised clinical trials (RCTs) in humans. Setting: RCTs comparing prompt closure versus gradual weaning of EVD in adult patients with hydrocephalus following aSAH were included. Participants: Patients aged equal to or greater than 18 years with an EVD due to hydrocephalus following aSAH were eligible for inclusion. Primary and secondary outcome measures: Primary outcomes were all-cause mortality, any serious adverse event, rate of ventriculoperitoneal (VP) shunt placement and quality of life. Secondary outcomes were patients with shunt failure, hospital and neuro intensive care unit (NICU) length of stay (LOS) and complications related to treatment with an EVD. Data permitted report of rate of VP shunt placement, and hospital and NICU LOS. Results: Six studies were assessed in full text. One RCT with 81 patients was included. Rate of VP shunt placement was 63.4% in the rapid weaning group (ie, prompt closure of the EVD; 41 patients) and 62.5% in the gradual weaning group (40 patients; p=0.932). LOS in hospital and NICU was significantly shorter in the rapidly weaned group compared with the gradually weaned group (mean 19.1 vs 21.5 days in hospital (p=0.03); and mean 14.1 vs 16.9 days in NICU (p=0.0002)). Data were insufficient to conduct meta-analysis, trial sequential analysis or subgroup analysis of heterogeneity and sensitivity. One RCT is currently ongoing. Conclusions: We found insufficient evidence to favour any of the two strategies for EVD discontinuation in patients with hydrocephalus following aSAH. PROSPERO registration number: CRD42018108801.